Desain Kemasan Produk Pouch Kartini Bordir Surabaya - Athika Dwi Wiji Utami; Masnuna; Houri Gita Semesta; Widyasari (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2023)
Kartini Embroidery Surabaya is a home-based business that produces various kinds of women's bags and wallets located in Surabaya. The bag and wallet products produced by Kartini Embroidery have a distinctive feature in the form of embroidered motifs embedded in each of their products, making them a differentiator from other competitors. However, Kartini Embroidered Products still do not have a packaging design that functions as a product identity and promotional tool. The packaging used for Kartini Embroidered products is still a plain mica box which only has the function of protecting the product from damage. The purpose of this design is to create a packaging design that has function as a product identity and a medium for conveying product information as a form of promotion. This design uses qualitative research methods by relying on primary data obtained from observations, interviews, and documentation. The data processing method is using SWOT analysis to evaluate internal and external conditions on products to determine the right strategy to increase business opportunities for Kartini Embroidery products. For further research, it is hoped that it will be able to carry themes related to strategic steps in increasing business opportunities in micro, small, and medium enterprises.